DIDACTIC SYSTEM OF SOCIALIZATION OF SCHOOLCHILDREN THROUGH LABOR AND PROFESSIONAL SKILLS - Mahmudova Darmonjon Bozorboyevna (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The following article is deals with the problem of socialization of the student's personality. The formation of labor and professional skills plays an important role in the socialization of the student's personality. In the article discussedthe types of work that contribute to the rapid socio-economic development of society, improving the pedagogical mechanisms of teaching innovative technologies in the labor market, and the didactic system of socialization of students based on advanced foreign experience and competency approach as well. The pedagogical possibilities of socialization of students through labor and professional skills, the content of the socialization process, the conditions for its implementation were identified, criteria for socialization of students through labor and professional skills were developed and applied to the pedagogical process, and the results were analyzed as well